A novel integrated thermal-/membrane-based solar energy-driven hybrid desalination system: Concept description and simulation results. (1st September 2016) - Kim, Young-Deuk; Thu, Kyaw; Ng, Kim Choon; Amy, Gary L.; Ghaffour, Noreddine
Abstract: In this paper, a hybrid desalination system consisting of vacuum membrane distillation (VMD) and adsorption desalination (AD) units, designated as VMD-AD cycle, is proposed. The synergetic integration of the VMD and AD is demonstrated where a useful effect of the AD cycle is channelled to boost the operation of the VMD process, namely the low vacuum environment to maintain the high pressure gradient across the microporous hydrophobic membrane. A solar-assisted multi-stage VMD-AD hybrid desalination system with temperature modulating unit is first designed, and its performance is then examined with a mathematical model of each component in the system and compared with the VMD-only system with temperature modulating and heat recovery units. The total water production and water recovery ratio of a solar-assisted 24-stage VMD-AD hybrid system are found to be about 21% and 23% higher, respectively, as compared to the VMD-only system. For the solar-assisted 24-stage VMD-AD desalination system having 150 m 2 of evacuated-tube collectors and 10 m 3 seawater storage tanks, both annual collector efficiency and solar fraction are close to 60%. Highlights: A hybrid desalination system consisting of VMD and AD units is proposed. A solar-assisted multi-stage VMD-AD hybrid system with TM unit is designed. Performance comparison between VMD-only and VMD-AD systems is performed. VMD-AD hybrid system achieves a 21% improvement in cumulative water production.